Correlation of Blood Alcohol Levels with Gamma Glutamyl Transferase in Fiberglass Factory Workers - Aisyah Aisyah; Tri Harningsih (Indonesian Journal of Global Health Research, 2025)
Alcohol is an organic compound in liquid form, colorless, with a specific odor, flammable, volatile, and miscible with water in all proportions. Fiberglass factories are among the industries that use ethanol in the production process and for testing product compatibility. Ethanol exposure can occur through inhalation, dermal contact, and ingestion. Chronic alcohol exposure may lead to liver dysfunction and an increase in Gamma Glutamyl Transferase (GGT) levels in the blood. This research aimed to determine the correlation between blood alcohol levels and Gamma Glutamyl Transferase in fiberglass factory workers. The research method used was analytical observational with a cross-sectional approach, employing a purposive sampling technique. The study sample consisted of 30 fiberglass factory workers exposed to alcohol and meeting the inclusion criteria. Data collection was conducted by measuring blood alcohol levels and Gamma Glutamyl Transferase levels using the enzymatic photometric method. Data analysis was performed using statistical tests to determine the correlation between blood alcohol levels and Gamma Glutamyl Transferase levels. Plasma or blood serum from the workers was used as samples. The alcohol levels were found to be 100% within normal ranges, and Gamma Glutamyl Transferase levels were normal in 93% of cases. Statistical tests using SPSS and Spearman correlation analysis yielded a significance value of 0.600 (p > 0.05), indicating no significant relationship between blood alcohol levels and Gamma Glutamyl Transferase in fiberglass factory workers.